TUGAS DAN FUNGSI BADAN PENANGGULANGAN BENCANA - Ni Ketut Sri Utari (University of Udayana, 2014)
The main issue of this research is the enactment of Act No. 24of 2007 regardingDisaster Management, there is a body of disaster management (BNBP and BPBDs) nationaland regional scale is still in charge, and on the other hand there is an Act No.23 /Prp/1959regarding the State of Emergency. Type of research is a normative law of the statut or yapproac hand the conceptualapproachto find the link between the two laws. The research found: (1) BNP Band BPBDmembership structure of the Steeringele mentis civilian officials, professional societies, andalso involves the military and police.(2) That the concept of disastersare handled by BNBP orBPBDs similar to the conditions of civil emergency due to natural disasters and social.Relationship between Act23/Prp/1959 with Act No. 24 of 2007, only in situations ofdisasterorstate of emergency status. Officials who have the authority to determine the statusof a state of emergency is the President, or the Governoror Regentequal to civil authorities inemergencies Act No.23/Prp/ 1959.(3) In an emergency situation, boththe law gives specialpowers to the rulers o fa state of emergency. Relations between the two laws is runningparalleland complementary.